> > Given: F(x) = x + 2 and G(x) = 3x + 5 (F + G) (x) =

Given: F(x) = x + 2 and G(x) = 3x + 5 (F + G) (x) =

Given: F(x) = x + 2 and G(x) = 3x + 5 (F + G) (x) =

109 Views

Given: F(x) = x + 2 and G(x) = 3x + 5 (F + G) (x) =

F(x) = x + 2 and G(x) = 3x + 5 (F + G) (x) =

Answer

f(x) = x + 2 g(x) = 3x + 5 (f + g)(x) = (x + 2) + (3x + 5) (f + g)(x) = (x + 3x) + (2 + 5) (f + g)(x) = 4x + 7

To see more answers head over to College Study Guides
Virtual Teaching Assistant: John B.
Question Level: Basic
Karma: Free
Upload Date: 5/31/2017

This 33 words question was answered by John B. on StudySoup on 5/31/2017. The question contains content related to Math Since its upload, it has received 109 views.

Recommended Questions